Respuesta :

The correct answer is the third option [tex] \frac{(4+9x)^3}{5x(x-1)} [/tex]

Explanation : 

The numerator 
9 times x ⇒⇒⇒ 9x
the sum of 4 and 9 times x ⇒⇒⇒ 4+9x
the cube of the sum ⇒⇒⇒ (4+9x)³

The denominator:
5 times x ⇒⇒⇒ 5x
the difference of x and 1 ⇒⇒⇒ x-1
the product of them ⇒⇒⇒ 5x(x-1)


Answer:
[tex] \frac{(4+9x)^3}{5x(x-1)} [/tex]

Explanation:
For the numerator:
the cube of the sum of 4 and 9 times x.
This is translated as:
a parentheses with the sum inside or (4+9x)
³ in the numerator 

For the denominator:
I product of two terms 5x and x-1.
This is translated as:
(5x)(x-1) in the denominator.

Combine them for:
[tex] \frac{(4+9x)^3}{5x(x-1)} [/tex]